Revitalisasi Desa Adat Budaya Hibua Lamo di Desa Kakara Lamo Kabupaten Halmahera Utara - Muhammad Rizal Syawal; Ernawati Hendrakusumah (UPT Publikasi Ilmiah Unisba, 2023)
Abstract. Hibualamo culture includes a system of government, kinship and marriage systems. In order to maintain cultural values ​​and preserve them with revitalization. The research method is qualitative research using an explorative approach. To find out the elements of Hibua Lamo culture and the factors that decrease the existence of Hibua Lamo culture in the traditional village of Kakara Lamo. Factors decreasing the existence of the Kakara Lamo traditional village, namely the change of indigenous peoples to a more modern society, mutual cooperation changes in society due to economic factors, traditional ceremonies are less participatory for indigenous peoples, Halu traditional houses are damaged, outside culture causes modern changes in cultural arts and marriage system. The revitalization of the Kakara Lamo Traditional Village is to revive the cultural identity of Hibualamo which is experiencing decline. Based on the results of the research above, the elements that need to be revitalized are traditional settlements, halu traditional houses, traditional ceremonies, and cultural arts. These revitalization steps can only occur if there is support from indigenous peoples, local government and the role of traditional institutions as local institutions that control the lives of indigenous peoples so that they can maintain cultural identity in the traditional village of Kakara Lamo. Abstrak. Budaya Hibualamo meliputi sistem pemerintahan, sistem kekerabatan dan perkawinan. Agar dapat mempertahankan nilai budaya dan melestarikannya dengan revitalisasi. Metode Penelitian yaitu Penelitian kualitatif dengan menggunakan pendekatan Eksploratif. Untuk mengentahui elemen-elemen budaya Hibua Lamo dan faktor-faktor penurunan eksistensi budaya Hibua Lamo di desa adat Kakara Lamo. Faktor-faktor penuruanan eksistensi desa adat Kakara Lamo yaitu perubahan masyarakat adat ke masyarkatan yang lebih modern, gotong royong perubahan masyarakat karna faktor ekonomi, upacara adat kurang partisipatif masyarakat adat, rumah adat Halu mengalami kerusakan, Budaya luar yang menyebabkan perubahan modern dalam seni budaya dan sistem perkawinan. Revitalisasi Desa Adat Kakara Lamo adalah menghidupakan kembali identitas budaya Hibualamo yang sedang mengalami kemunduran. Berdasarkan hasil peneleitian di atas maka elemen-elemen yang perlu direvitalisasi yaitu permukiman adat, rumah adat halu, upacara adat, dan seni budaya. Langkah-langkah revitaliasi ini baru bisa terjadi jika mendapat dukungan masyarakat adat, pemerintah daerah dan peran lembaga adat sebagai institusi lokal yang mengotrol kehidupan masyarakt adat agar dapat menjaga identitas budaya di desa adat Kakara Lamo.